2007
DOI: 10.4049/jimmunol.178.2.858
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Hemopoietic Precursors Commit to the T Cell Lineage Only after Arrival in the Thymic Microenvironment

Abstract: T lymphocytes develop in the thymus from hemopoietic precursors that commit to the T cell lineage under the influence of Notch signals. In this study, we show by single cell analyses that the most immature hemopoietic precursors in the adult mouse thymus are uncommitted and specify to the T cell lineage only after their arrival in the thymus. These precursors express high levels of surface Notch receptors and rapidly lose B cell potential upon the provision of Notch signals. Using a novel culture system with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 70 publications
8
81
1
Order By: Relevance
“…Flow cytometry analysis showed greater binding by Dll4-Fc to DN thymocytes than the Dll1-Fc protein (Supplemental Fig. 2), consistent with previous reports (20,33). In addition, Dll4-Fc also showed increased binding to EL4 and SL12 cell lines, compared with Dll1-Fc (Supplemental Fig.…”
Section: Dn3 Stage In Op9-dl4supporting
confidence: 80%
“…Flow cytometry analysis showed greater binding by Dll4-Fc to DN thymocytes than the Dll1-Fc protein (Supplemental Fig. 2), consistent with previous reports (20,33). In addition, Dll4-Fc also showed increased binding to EL4 and SL12 cell lines, compared with Dll1-Fc (Supplemental Fig.…”
Section: Dn3 Stage In Op9-dl4supporting
confidence: 80%
“…While the expression data for the Notch ligands seems mostly consistent with data in the mouse, with perhaps the exception of the high Jag2 expression levels that still need confirmation at the protein level (Heinzel et al, 2007), some differences can be observed between both species with respect to the expression patterns of the Notch receptors. While TSPs (population A) express both NOTCH1 and NOTCH2, but not NOTCH3, uncommitted CD34 + CD1 -human postnatal thymocytes (population B) express, in addition to NOTCH1 and NOTCH2, also significant levels of NOTCH3, and this expression persists into the DP stages of T cell development (populations C-G) before shutting down in mature CD4 and CD8 SP cells (population H) Ghisi et al, 2011).…”
Section: Notch Signaling Profilementioning
confidence: 65%
“…Although there is clear detectable Notch3 expression at the DN2 stage when  and  T cells start to diverge (Shi et al, 2011), it is unclear if these levels are sufficient to mediate these developmental processes, especially because recent data revealed no obvious defect in mouse  T cell development in the absence of Notch3 (Shi et al, 2011;Suliman et al, 2011). In addition, it is unclear how much Jagged2 protein is expressed by the TECs of the mouse, and in situ RNA expression analysis suggests that DLL4 is more abundantly expressed in the mouse cortex compared with Jagged2 (Heinzel et al, 2007), raising the possibility that Notch3 might not be sufficiently activated to mediate this early developmental T cell choice. Nevertheless, the observation that Jagged2-deficient mice display a reduction in fetal  T cell development is consistent with our human findings (Jiang et al, 1998).…”
Section: Discussionmentioning
confidence: 98%